2007
DOI: 10.2320/matertrans.mra2007616
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO<SUB>2</SUB> Nanotubes and Their Photocatalytic Properties in Degradation Methylcyclohexane

Abstract: The tubular TiO 2 photocatalysts were successfully synthesized by hydrothermal method. The external tube diameters fall in 8 and 12 nm and the internal diameters are between 5 and 8 nm. Moreover, the lengths of the nanotubes are up to 500 nm and the specific surface area increases to 330 m 2 /g, while TiO 2 powders are 78 m 2 /g. Methylcyclohexane (MCH) was selected as the target pollutant to investigate the photocatalytic performance. The results indicate that TiO 2 nanotubes accelerate the degradation of MCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
(16 reference statements)
2
18
0
Order By: Relevance
“…They also reported that the specific surface area of n-TiO 2 greatly increased after washing with distilled water and HCl. In agreement with that, Liu et al [105] found that the surface area of n-TiO 2 was 78 m 2 /g following the alkaline hydrothermal reaction. However, the surface area was increased to 330 m 2 /g after washing with HCl.…”
Section: Synthesis Of N-tio 2 Using the Alkaline Hydrothermal Reactionsupporting
confidence: 87%
“…They also reported that the specific surface area of n-TiO 2 greatly increased after washing with distilled water and HCl. In agreement with that, Liu et al [105] found that the surface area of n-TiO 2 was 78 m 2 /g following the alkaline hydrothermal reaction. However, the surface area was increased to 330 m 2 /g after washing with HCl.…”
Section: Synthesis Of N-tio 2 Using the Alkaline Hydrothermal Reactionsupporting
confidence: 87%
“…Pores can be classified into two types: open and closed. Particularly, the extent of open pores is considered as an important factor for the filter 6,7) as fluid permeability highly depends on the value. Hence, controlling the pore structure of porous materials is a very important process necessary for the application to filters.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is an environmental catalyst widely used in the photocatalyst area for water and air purification, [7][8][9][10] solar cells elaboration, 11) and so on. When TiO 2 exists in anatase phase, it is known to have greater ability as a photocatalyst than rutile phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to a rapid shift in the bacterial composition of dental plaque, most notably in the number of acidogenic bacteria, such as S. Mutans [2,21] and this shift may persist throughout and beyond a course of treatment [22]. The first sign of demineralisation may be the development of WSL on the enamel surface around the bracket margins, which if left unchecked can progress to cavitation.…”
Section: Antibacterial Testing Of Ag-tio2 Powders Under Visible Lightmentioning
confidence: 99%